(untitled) (European Journal of Social Sciences, 2019)
Indigenous Bapedi music and oral tradition have been dismissed as myth, superstition and primitive stories. Such dismissal has been based on the misconception and assumption that indigenous Bapedi music and oral tradition are proletarian, steeped in evil religious experiences and unacceptable for worship. In Bapedi society, indigenous music and traditional oral stories are utilized to buttress and demonstrate the collective wisdom of Bapedi people, as well as to transmit Bapedi culture, values, beliefs and history from generation to generation. This article examines misconceptions about indigenous Bapedi music and traditional oral stories. It argues that indigenous Bapedi music and oral tradition should not be dismissed at face value as practices overtaken by circumstances and hence irrelevant to the present Bapedi community developmental needs. The findings of the present study faithfully reflect that indigenous Bapedi songs and traditional oral stories resonate in people’s personal lives, in religious rituals and in society at large. These findings suggest that Bapedi people should keep and perpetuate their valuable heritage, which is still needed for survival and for the welfare of our next generation. The main question the study addressed is: What role do indigenous Bapedi music and oral tradition play in Bapedi culture?